2017
DOI: 10.1002/lno.10631
|View full text |Cite
|
Sign up to set email alerts
|

Carbon budget of a shallow, lagoonal estuary: Transformations and source‐sink dynamics along the river‐estuary‐ocean continuum

Abstract: A comprehensive carbon budget was constructed to quantify carbon flows through the freshwater‐marine continuum of a temperate, microtidal estuary. We performed coordinated measurements of dissolved inorganic carbon and total organic carbon fluxes to resolve spatial variability between and along the channel and shoals and diel variability across the entire estuary for 2 yr. Net ecosystem metabolism (NEM) was the most significant control on carbon flow within estuary regions. However, metabolic rates were spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 63 publications
5
41
1
Order By: Relevance
“…Both estuaries were divided into three morphologically distinct sections along their respective longitudinal axes (Figure ), such that each estuary's mouth is the point at which other watersheds become influential. These divisions are consistent with previous studies in the NeuseRE (Crosswell et al, ) and NewRE (Crosswell et al, ). In situ p CO 2 was measured using a combined laminar flow showerhead equilibrator and infrared detector (LI‐COR, Li‐840A).…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Both estuaries were divided into three morphologically distinct sections along their respective longitudinal axes (Figure ), such that each estuary's mouth is the point at which other watersheds become influential. These divisions are consistent with previous studies in the NeuseRE (Crosswell et al, ) and NewRE (Crosswell et al, ). In situ p CO 2 was measured using a combined laminar flow showerhead equilibrator and infrared detector (LI‐COR, Li‐840A).…”
Section: Methodssupporting
confidence: 93%
“…Estuaries often receive large allochthonous organic matter loads, which support high remineralization rates and drive them toward net ecosystem heterotrophy and CO 2 degassing (Bauer et al, ; Borges & Abril, ; Cai, ; Frankignoulle et al, ). At the same time, nutrients (nitrogen and phosphorus) supplied externally or recycled internally drive high rates of autochthonous organic matter production in these ecosystems, causing some estuaries to act as CO 2 sinks (Crosswell et al, , ; Drupp et al, ; Hunt et al, ; Maher & Eyre, ). The balance between these factors varies over space and time, making it difficult to globally integrate CO 2 fluxes across these diverse ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…We believe the most appropriate value falls between these estimates. Overall, CO 2 emissions from the NRE‐PS were about an order of magnitude less than lateral C fluxes, which were dominated by DOC, a result consistent with prior events (Table ; Crosswell et al, ).…”
Section: Resultssupporting
confidence: 81%
“…An EC footprint analysis (Kljun et al, ) indicates that the data screening steps were successful in limiting CO 2 flux measurements to those entirely within the aquatic domain, suggesting that adjacent forested and urban regions did not affect measured CO 2 flux (Figure S1). Averaged over the entire study period, CO 2 flux was 0.31 ± 1.4 mmol·m −2 ·hr −1 , nearly half of the 0.68 average reported in Van Dam, Crosswell, Anderson, et al () for the New River estuary and within the range reported in Crosswell et al () for 2013–2014 and 2014–2015 (−0.023 and 2.3 mmol·m −2 ·hr −1 , respectively) for the same estuary. Winds were generally moderate, not exceeding 14 m/s as a 30‐min average and were dominated by a sea breeze, land breeze oscillation (Figure d).…”
Section: Resultssupporting
confidence: 76%